2014
DOI: 10.1111/1365-2656.12198
|View full text |Cite
|
Sign up to set email alerts
|

A critical examination of indices of dynamic interaction for wildlife telemetry studies

Abstract: Summary 1.Wildlife scientists continue to be interested in studying ways to quantify how the movements of animals are interdependent -dynamic interaction. While a number of applied studies of dynamic interaction exist, little is known about the comparative effectiveness and applicability of available methods used for quantifying interactions between animals. 2. We highlight the formulation, implementation and interpretation of a suite of eight currently available indices of dynamic interaction. Point-and path-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
152
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(154 citation statements)
references
References 80 publications
2
152
0
Order By: Relevance
“…When considering dyadic interactions, we found many asymmetric responses, mostly one‐sided behaviours in which an individual is attracted to or avoids another, neutrally behaving one, which would remain undetected in classical dyadic analyses (e.g. Long et al, ). In light of our simulation analysis of mixed behaviours, the relatively large number of non‐significant interaction coefficients, especially for males, might indicate that those individuals switched their behaviours during the observation period.…”
Section: Discussionmentioning
confidence: 86%
“…When considering dyadic interactions, we found many asymmetric responses, mostly one‐sided behaviours in which an individual is attracted to or avoids another, neutrally behaving one, which would remain undetected in classical dyadic analyses (e.g. Long et al, ). In light of our simulation analysis of mixed behaviours, the relatively large number of non‐significant interaction coefficients, especially for males, might indicate that those individuals switched their behaviours during the observation period.…”
Section: Discussionmentioning
confidence: 86%
“…To measure how strongly correlated were the movements of the two deer comprising each dyad, we used the dynamic interaction metric of Long et al (2014). This metric generalizes the vector correlation coefficient of Shirabe (2006) to allow examination of short time periods and does not involve physical proximity.…”
Section: Methodsmentioning
confidence: 99%
“…Attraction and avoidance can be inferred from concurrent movements of neighboring animals (88,89), providing important insight into the behavioral processes underlying the territorial dynamics of individuals (90,91) and groups (88,92). For example, simultaneous tracking has revealed that the outcome of competitive interactions between neighboring primate social groups depends more strongly on the location of the encounter than the relative size of the groups and has documented the costs of losing territorial interactions (93,94,95).…”
Section: Science Sciencemagorgmentioning
confidence: 99%